Poor self-rated health is associated with sedentary behavior regardless of physical activity in adolescents - PeNSE study. - Tebar, William R. [UNESP]; Werneck, André O. [UNESP]; Silva, Danilo R.P.; de Souza, Jefferson M. [UNESP]; Stubbs, Brendon; da Silva, Claudiele C.M. [UNESP]; Ritti-Dias, Raphael M.; Christofaro, Diego G.D. [UNESP] (Elsevier, 2021)
Objectives: To analyze the independent and combined associations of physical activity (PA) and sedentary behavior (SB) with self-rated health (SRH) in a large sample of adolescents. Methods: Data from 100,873 students with mean age of 14.3 (±1.1) years were analyzed. SRH, PA and SB were assessed by questionnaires. Age, ethnicity, maternal education, geographical region of country, type of city, industrialized and sugary foods consumption were covariates. Logistic regression models were used to analyze the data according to gender. Results: ≥300 min/week of PA [OR:1.12 (95%CI:1.04–1.21)] and <4 h of sitting time [OR:1.42 (95%CI:1.32–1.54)] were associated with good SRH among boys, while only lower sitting time was associated with good SRH among girls [OR:1.32 (95%CI:1.23–1.41)]. Physically active and with low sitting time adolescents were more likely to have good SRH [Boys OR:1.57 (95%CI:1.41–1.75); Girls OR:1.32 (95%CI:1.18–1.46)], than inactive and with high sitting time counterparts. However, high sitting time was associated with poor SRH independently of ≥300 min/week of PA. Conclusion: PA and sitting time were independently associated with SRH in Brazilian adolescents. Moreover, reaching ≥300 min/week of PA was not sufficient to attenuate the negative association between high sitting time and SRH.
Keywords: Exercise; Health perception; Sedentary behavior; Youth